PENGEMBANGAN MEDIA PEMBELAJARAN MENGGUNAKKAN SOFTWARE MINDJET MINDMANAGER PADA AKUNTANSI DASAR SMK KELAS X AKL - Saadah, Elit Aminatus (Inspiratif Pendidikan, 2021)
The purpose of this study is to 1) determine the process of developing mind mapping media using mindjet mindmanager 2017 software for basic accounting subjects for Vocational High School class X AKL, 2) to be able to determine the feasibility level of mind mapping media made by researchers for class X AKL with basic accounting. as a subject, 3) to be able to find out the response to vocational students in class X AKL regarding the mind mapping media developed by researchers. The type in this research is the development with the 4D Thiagarajan model with four stages, namely the first stage of defining, the second stage of planning, the third stage of development and finally the stage of deployment. This development research uses review sheets and expert validation and student response questionnaires as research instruments. The learning media was tested on 20 class X AKL vocational students from SMK Ketintang Surabaya. Mind mapping learning media get criteria of "feasible" with a percentage of 79% of material experts and criteria of "very feasible" with a percentage of 87% of media experts. Meanwhile, the student response got the criteria of "very good" with a percentage of 95%. Based on the explanation above, it can be stated that mind mapping media is feasible to be used in learning basic accounting material.